Ответы и объяснения

2013-09-15T15:23:40+04:00
Решение на фото                                                    
  • Участник Знаний
2013-09-15T15:29:42+04:00
1) R^3*S^3 * ( S + R)
2) 5A^3*X*( 4 - 3AX)
3) (X - 3)*(X + 3)
4) ( 1 - 5Y)*(1 + 5Y)
5) (3X - 2X^2) + ( 3Y - 2XY) = X*(3 - 2X) + Y*(3 - 2X) = ( 3 - 2X ) * ( X + Y )
6) (20Z^2K - 5K) + (2Z + 1) = 5K*(4Z^2 - 1) + (2Z + 1) = 5K*(2Z - 1)*(2Z + 1) +
+ (2Z + 1) = (2Z + 1)*(2Z +1)*(2Z - 1)*5K
7) 16T^2 + S^2*(8T + S^2) = 2*(8T + S^2)*(8T + S^2)
8) B^4 - 16C*(B^2 + 4C) = (B^2 - 4C)*(B^2 + 4C)